2016
DOI: 10.3906/elk-1412-207
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of wind speed probability distributions for wind power assessment of four sites

Abstract: Abstract:In this paper, five probability distribution functions are employed to fit the wind speed data from four different geographical locations in the world in a preliminary analysis. These wind regimes are selected such that they represent wide ranges of mean wind speeds and present different shapes of wind speed histograms. The wind speed data used for modelling consist of 10-min average SCADA data from three US wind farms and hourly averages recorded at a weather station in Canada. Out of the five, three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 30 publications
0
38
0
1
Order By: Relevance
“…Pearson VI, uniform, and Weibull distribution functions[32] [33][34]. On our study site, it has been demonstrated that the Weibull distribution with two parameters (shape parameter and scale parameter) developed in 1951 by Waloddi Weibull is suitable to analyze and represent the wind rate distribution.…”
mentioning
confidence: 99%
“…Pearson VI, uniform, and Weibull distribution functions[32] [33][34]. On our study site, it has been demonstrated that the Weibull distribution with two parameters (shape parameter and scale parameter) developed in 1951 by Waloddi Weibull is suitable to analyze and represent the wind rate distribution.…”
mentioning
confidence: 99%
“…(2) Parameters obtained by evolutionary techniques for SCADA data in [1] 4PL [34,35] = = maximum asymptote = asymmetry factor (parameters obtained by evolutionary techniques) curve by using the equation of a straight line. The resulting curve follows the actual curve more accurately.…”
Section: Polynomial Function Approximationmentioning
confidence: 99%
“…It is shown in [1] that this model can be used for online monitoring of power curves. Another form of four PL expression is used for extracting power curve from actual wind speed and power curve data of a wind farm in [35]. The method is applied for wind energy estimation of the selected wind farm site.…”
Section: Journal Of Energymentioning
confidence: 99%
See 1 more Smart Citation
“…In [13], a three-parameter logistic function (3-PLF) was used by the authors to evaluate the performance of the Gamsesa G90-2.0 MV wind turbine. Many researchers suggested using a four-parameter logistic function (4-PLF) to model WTPC [14,15]. When the variable asymmetry factor is added into the above 4-PLF, a five-parametrer logistic function (5-PLF) can be derived.…”
Section: Introductionmentioning
confidence: 99%